POTRET PENDIDIKAN DAN KOMPETENSI GURU DI DAERAH PERBATASAN KABUPATEN SANGGAU - Samion; Darma, Yudi (JURNAL BORNEO AKCAYA, 2016)
This study intends to conduct a study on the needs and competencies of teachers and border area development of education in District Entikong Sanggau West Borneo as an alternative means of problem solving to provide solutions as a foothold in the revitalization of educational equity in the border area. Data for this study were obtained from Cabdikpora, teachers and informants related. The techniques used for data collection was a survey and interview techniques. Data collection tool consists of methods of documentation, questionnaires and interview guides to collect qualitative information from the data source. The data were processed using descriptive analytic method. Issues raised in this study is the need and competence of teachers in the development and inhibiting factors in education based on the implementation. The findings of this study suggest that the urgency and attention management, and implementation of government policies for the development of human resources through education Entikong is needed. Collection is shows that the relevance of the teacher in the District border area Entikong still not proportionate and relevant, and should be done regularly coaching, and intensive scheduled to increase each line competency of teachers, both pedagogic competence, personality, professional, and socially by the local education office. Therefore, in order to provide guidance cabdikpora a comprehensive, well improved coordination between the members and managers of education in the district and the district education units and educators, improve access to information, to evaluate the data collection on a regular basis for the benefit of the administration and implementation of the completeness of data collection of learning, as a means of monitoring and evaluation for the parameters of the program's success in education and policy makers as a follow-up . Participate in the provision of facilities and infrastructure in procuring gradually related to the completeness of supporting the implementation of learning (laboratory equipment, technology, learning resources, instructional media, and so on), improve quality of service for the management, monitoring and evaluation as well as preparing and placing teachers who according to its competence